Postanaesthetic effects of ketamine–midazolam and ketamine–medetomidine on gastrointestinal transit time in rabbits anaesthetised with isoflurane. (29th February 2020) - Botman, Julie; Hontoir, Fanny; Gustin, Pascal; Cambier, Carole; Gabriel, Fabien; Dugdale, Alex; Vandeweerd, Jean‐Michel
Abstract : Background: Gastrointestinal stasis is a common perianaesthetic complication in rabbits. The objective of this study was to assess the impact on gastrointestinal transit time of ketamine–midazolam (KMZ) versus ketamine–medetomidine (later antagonised by atipamezole) (KMT‐A) in rabbits anaesthetised with isoflurane. Methods: This was a cross‐over, randomised, single‐blinded, controlled, experimental trial. Seven healthy adult New Zealand White rabbits were used. Gastrointestinal transit time was assessed by contrast radiography in awake rabbits. Presence of contrast medium in the small intestine (gastric transit time), in the caecum (small intestinal transit time) and in faeces in the colon was assessed. One week later, 55 minutes isoflurane anaesthesia was induced with ketamine (15 mg/kg) and either midazolam (3 mg/kg) or medetomidine (0.25 mg/kg) by intramuscular injection. Thirty minutes after discontinuation of isoflurane, atipamezole (0.5 mg/kg) was administered only to rabbits in KMT‐A treatment. Gastrointestinal transit time was then assessed in both treatment groups, beginning 30 minutes after cessation of isoflurane administration. Two weeks later, the treatment groups were interchanged. Results: Gastric and small intestinal transit times were significantly longer with KMT‐A (92±109 minutes and 214±119 minutes, respectively) than with KMZ (1±0 minutes and 103±6 minutes, respectively) and in the awake state (7±7 minutes and 94±32 minutes, respectively). Conclusion: Clinicians should therefore be aware of the potential gastrointestinal side effects of KMT‐A, particularly in rabbits at risk for gastrointestinal stasis.